Wearable Surface‐Lighting Micro‐Light‐Emitting Diode Patch for Melanogenesis Inhibition. Issue 1 (11th November 2022) - Lee, Jae Hee; Ahn, Yuri; Lee, Han Eol; Jang, You Na; Park, A. Yeon; Kim, Shinho; Jung, Young Hoon; Sung, Sang Hyun; Shin, Jung Ho; Lee, Seung Hyung; Park, Sang Hyun; Kim, Ki Soo; et al.
Abstract: Wearable light‐emitting diode (LED)‐based phototherapeutic devices have recently attracted attention as skin care tools for wrinkles, acne, and hyperpigmentation. However, the therapeutic effectiveness and safety of LED stimulators are still controversial due to their inefficient light transfer, high heat generation, and non‐uniform spot irradiation. Here, a wearable surface‐lighting micro‐LED (SµLED) photostimulator is reported for skin care and cosmetic applications. The SµLEDs, consisting of a light diffusion layer (LDL), 900 thin film µLEDs, and polydimethylsiloxane (PDMS), achieve uniform surface‐lighting in 2 × 2 cm 2 ‐sized area with 100% emission yields. The SµLEDs maximize photostimulation effectiveness on the skin surface by uniform irradiation, high flexibility, and thermal stability. The SµLED's effect on melanogenesis inhibition is evaluated via in vitro and in vivo experiments to human skin equivalents (HSEs) and mouse dorsal skin, respectively. The anti‐melanogenic effect of SµLEDs is confirmed by significantly reduced levels of melanin contents, melan‐A, tyrosinase, and microphthalmia‐associated transcription factor (MITF), compared to a conventional LED (CLED) stimulator. Abstract : A wearable surface‐lighting micro‐LED (SµLED) photostimulator is reported for skin‐bleaching applications. The SµLEDs, consisting of a light diffusion layer (LDL), 900 thin film µLEDs, and polydimethylsiloxane (PDMS), achieve uniform surface‐lighting in 2 × 2 cm 2 ‐sized area with 100% emission yields. The SµLEDs maximize melanogenesis inhibition effect on the skin surface by uniform irradiation, high flexibility, and thermal stability.